Foreign Direct Investment as a Catalyst for Growth in ECOWAS: Revisiting the Role of Financial Development - Mohamed Lamin Conteh; Linda Rosalina; Unggul Heriqbaldi (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: This study examines the impact of foreign direct investment (FDI) and financial development on economic growth across ten ECOWAS nations from 2000 to 2023. It aims to answer two main questions: whether FDI plays a significant role in boosting economic growth in ECOWAS countries, and whether the level of financial development influences this relationship. Approach: Using dynamic panel econometric techniques, the vector error correction model (VECM) and fully modified ordinary least squares (FMOLS), the study investigates the short- and long-run effects of FDI and financial development on growth. Control variables include gross capital formation, population growth, and trade openness, with data from the World Bank and IMF databases. Findings: FDI has a positive and significant impact on economic growth in both the short and long term, whereas financial development is statistically insignificant. This implies that the region’s underdeveloped financial systems limit the advantages of FDI. FMOLS results verify the stability of FDI’s long-term effects and highlight the vital role of trade openness. Originality/Value: This study contributes to the literature by employing dynamic panel techniques (VECM and FMOLS) on updated data from 2000 to 2023 for the ECOWAS region. It reevaluates the relationship between FDI and growth in the context of regional integration and post-pandemic recovery. Unlike earlier static models, it examines how financial development can serve as a channel for enhancing the impact of FDI. Policy Implications: The findings emphasize the importance of reforming the financial sector, enhancing access to credit, and bolstering institutional frameworks to utilize FDI inflows better. Enhancing financial intermediation and governance is crucial to transforming FDI-driven growth into sustainable, inclusive development aligned with the Sustainable Development Goals (SDGs).